Kredibilitas Komunikator Dalam Kasus Satinah dan Kasus Kendeng - Puteri, Yovanca Natalia Pradipta; Siahaineni, Royke R.; Sari, Dewi Kartika (Komunikator, 2018)
Melanie Subono involvement on the case of Satinah and Kendeng is interested, which is followed by majority of netizen called Indonesia society. Success in completing a case is determined by actress in building of communication network so as to achieve the goal. This research uses the theory of Communication Network and Social Movement which aims to know how does Melanie Subono as an actress build communication network through media social and make social movement to achieve the goal. After Communication Network and Social Movement formed, this research also uses Communicator Credibility to see all factors of communicator credibility which is played by Melanie Subono in the case of Satinah and Kendeng. This research aims to know how to build Communication Network and Social Movement, and also to know Communicator Credibility of Melanie Subono on the case of Satinah and Kendeng. The result of this research obtained is the relations in the case of Satinah and Kendeng obviously and determining the success in solving the case. Social movement which Melanie Subono did in the case of Satinah is type of Alternative Moment and type of social movement in the case of Kendeng is Reformative Moment. Communications network built and social movements to determine the credibility of Melanie Subono be communicators.